Feasibility of cattle urine as nutrient medium for the microalgal biomass production - A. Suresh; S. Tamilvanan; K. Harini; H.V. Seventhi; R. Deepan Guna; R. Mahalakshmi; S. Suriyapriya; D. Sharmila; M. Thenmozhi (Global Journal of Environmental Science and Management)
Thenutrient medium used for the cultivation of microalgae adds more cost to its value-added product as well as the commercial scale application. Therefore in this study, focused feasibility of cattle urine as a cheap source of nutrients for microalgal growth, because, it contains various minerals and economical which may support the growth of microalgae and reduce the medium cost. To check this, fresh cattle urine was collected, characterized, diluted and inoculated microalgae species Oscillatoria-SRA (Stagnant rainwater algae), Oscillatoria-CWA (Cooum waste algae), Chlorella and Synecocystis separately and incubated under fluorescent light with 8 hours light and 16 hours dark cycle. The biomass was quantified after 15 days and found out variation in biomass quantity in all microalgae isolates. The maximum of 2.6 g/L biomass was produced in Chlorella sp., at 10% urine, followed by Synechocystis sp., (2.25 g/L in 10% urine), Oscillatoria sp.,-SRA (1.3 g/L in 5% urine) and Oscillatoria sp.,-CWA (0.3 g/L in 1% urine). Moreover, lipid quantity was shown at the maximum of 12% dry weight in Oscillatoria sp-SRA., trailed by the 10% in Chlorella sp., 7% in Synecocystis sp., and the least of 5% in Oscillatoria sp-CWA. This study divulged that cattle urine alone is being able to support microalgae growth at a significant amount, thus convalescing industrial production of microalgae ultimately will reduce the cost of microalgal value-added products.